Implementasi Figma Dalam Pengembangan Prototipe Situs Usaha Rintisan Nominus - Juang Prayoga Jati, Surya; Hasbi, Imanuddin (eProceedings of Management, 2024)
In creating a website, designers are required to create a website that suits human needs, habits, and capabilities. Tofulfill these requirements, designers need tools that can be used, one of which is Figma because this software hasseveral advantages. In developing the NoMinus online shop. Writer uses the Empathy Map to provide comprehensiveinformation about user satisfaction and disappointment when interacting with existing online buying and sellingwebsites. The results of testing through quisionnaries showed that the user interface and user experience of the existingonline shop website received a variety of responses from users. After getting that result, writer created a websiteprototype based on the existing test results. The prototype that the writer has created is an online shop website that isexpected to meet customer needs and make the NoMinus online shop website be a user-friendly website.Keywords-NoMinus, website, empathy map, Figma, prototype